2018
DOI: 10.21037/jtd.2018.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Non-intubated thoracoscopic bullectomy under sedation is safe and comfortable in the perioperative period

Abstract: Background: Non-intubated thoracoscopic surgery can be performed under sedation using adjuvant regional anesthesia, however, the benefits of non-intubated thoracoscopic surgery under sedation have not yet been completely verified. In this study, we compare the perioperative safety and pain complaints of sedation without intubation in thoracoscopic bullectomy with that of conventional general anesthesia with double-lumen intubation and mechanical ventilation. Methods: Forty-one patients with primary spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Unlike previous studies [5][6][7][8][9], paravertebral block was performed before anesthesia induction in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previous studies [5][6][7][8][9], paravertebral block was performed before anesthesia induction in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, adverse events such as sore throat, pain, hoarseness, and respiratory complications are not uncommon after conversional intubation and general anesthesia [3][4]. Compared with general anesthesia with intubation, nonintubated anesthesia can obviously reduce the adverse events described above, a phenomenon that has aroused great interest of thoracic surgeons in the past decade [5][6][7][8][9]. A previous study con rmed that nonintubated video-assisted thoracoscopic surgery (VATS) is safe and feasible for multiple thoracic conditions, without risk of complications caused by conversional intubation or general anesthesia [10].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous studies [5][6][7][8][9], paravertebral block was performed before anesthesia induction in our study. Previous study showed preemptive pharmacological blockade had been effectively used in surgical patients with satisfactory results [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, adverse effects such as sore throat, pain, hoarseness, and respiratory complications are not uncommon after conversional intubation and general anesthesia [3][4]. Compared with general anesthesia with intubation, non-intubated anesthesia can obviously reduce above adverse events, which has aroused great interest in thoracic surgery in the past decade [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 , 21 ] And the intraoperative PaCO 2 level (mean 57.0 mm Hg) in the study group did increase significantly because of “re-breathing” of exhaled air and respiratory depression, but returned to normal values 1 hour after surgery, furthermore considering that many studies describe a transient intraoperative hypercapnia, this value is still tolerable. [ 22 24 ] In fact, the use of spontaneous breathing inhalation anesthesia can permit a self-limiting regulation of the inhaled gas, thus avoiding the occurrence of severe respiratory depression. In addition, the presence of ILMA can safely and easily manage any possible respiratory depression, which were reported during thoracoscopy performed under sedation-assisted local anesthesia by Chhajed et al [ 25 ] Therefore, in our study, because of the use of ILMA, no patients were converted to tracheal intubation due to hypoxemia and hypercapnia.…”
Section: Discussionmentioning
confidence: 99%